Benefits of an object-oriented database representation for controlled medical terminologies. - Gu H; Halper M; Geller J; Perl Y; Gu, H; Halper, M; Geller, J; Perl, Y (Journal of the American Medical Informatics Association, 1999)
Objective: Controlled medical terminologies (CMTs) have been recognized as important tools in a variety of medical informatics applications, ranging from patient-record systems to decision-support systems. Controlled medical terminologies are typically organized in semantic network structures consisting of tens to hundreds of thousands of concepts. This overwhelming size and complexity can be a serious barrier to their maintenance and widespread utilization. The authors propose the use of object-oriented databases to address the problems posed by the extensive scope and high complexity of most CMTs for maintenance personnel and general users alike.Design: The authors present a methodology that allows an existing CMT, modeled as a semantic network, to be represented as an equivalent object-oriented database. Such a representation is called an object-oriented health care terminology repository (OOHTR).Results: The major benefit of an OOHTR is its schema, which provides an important layer of structural abstraction. Using the high-level view of a CMT afforded by the schema, one can gain insight into the CMT's overarching organization and begin to better comprehend it. The authors' methodology is applied to the Medical Entities Dictionary (MED), a large CMT developed at Columbia-Presbyterian Medical Center. Examples of how the OOHTR schema facilitated updating, correcting, and improving the design of the MED are presented.Conclusion: The OOHTR schema can serve as an important abstraction mechanism for enhancing comprehension of a large CMT, and thus promotes its usability.